Representative farms economic outlook for the December 2012 FAPRI/AFPC Baseline - James W. Richardson; Joe L. Outlaw; George M. Knapek; J. Marc Raulston; Brian K. Herbst; David P. Anderson; Steven L. Klose (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2012)
The Agricultural and Food Policy Center (AFPC) at Texas A&M University develops and maintains data to simulate 95 representative crop, dairy, and livestock operations in major production areas in 28 states. The chief purpose of this analysis is to project the economic viability of those farms by region and commodity for 2012 through 2017. The data necessary to simulate the economic activity of these operations is developed through ongoing cooperation with panels of agricultural producers in selected states. The Food and Agricultural Policy Research Institute (FAPRI) provided projected prices, policy variables, and input inflation rates in their December 2012 Baseline. Under the December 2012 Baseline, 49 of the 63 crop farms are considered in good liquidity condition (less than a 25 percent chance of negative ending cash by 2017). Two crop farms have between a 25 percent and a 50 percent likelihood of negative ending cash, and the remaining 12 crop farms have greater than a 50 percent chance of negative ending cash. Furthermore, 48 of the 63 crop farms are considered in good equity position (less than a 25 percent chance of decreasing real net worth during the study period). Six crop farms have between a 25 percent and 50 percent likelihood of losing real net worth, and nine crop farms have greater than a 50 percent probability of decreasing real net worth. The following discussion provides an overall evaluation by commodity considering both liquidity and equity measures.
Keywords: 330